Improduktivitetsstudie vid lastning av bilfartyg - En studie av Lean-teorins möjlighet att reducera slöseri - Hjertquist, Richard; Ljunggren, Rasmus (My University, 2016)
This study is conducted in cooperation with Logent Ports & Terminals Gothenburg and focuses on the unproductive time arising in connection with the loading of car carrier vessels. The study is intended to enable greater productivity in production by studying waste. The study is rooted in the Japanese production theory, Lean production, which aims to reduce all non-value-added operations. The study focuses on the improvements that can be made in the process of loading the cars. The study objective was to locate unproductive sequences and measure these, study the time required for the tally process and to discuss applicable tools within Lean on the loading process. The methodology for the report has been to study the theory of Lean production and all process-enhancing tools that the theory concludes. Information on how the terminal operates in conjunction with a loading sequence and the dividing of the car-crews are explained in the report. The workflow is described and then studied along with the loading procedure, where the main factors that contributed to the unproductive time were located. Measurements were executed on the time it takes for the cars to be stowed onboard and the time of the tally procedure. The measurements were pasted using a statistical tool where the results, afterwards were interpreted and analyzed. In the results and the discussion section all the measured results are presented together with an interpretation and analysis of them. The results of the measurements clearly showed that the parking time contributes to unproductive time, and that there are measures that can improve production efficiency. This section also concludes a discussion of whether it is possible to apply any of the tools in the Lean theory at an actual loading sequence. Possibilities for future solutions are discussed to create a better flow and reduce unproductive time.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics